HUBUNGAN PERAN KELUARGA DENGAN PRAKTEK PEMBERIAN MAKANAN PENDAMPING ASI PADA BAYI UMUR 6-24 BULAN DI KABUPATEN JEMBER [CORRELATION BETWEEN FAMILY OF ROLES AND COMPLEMENTARY BREAST FEEDING PRACTICES AMONG CHILDREN AGED 6-24 MONTHS IN JEMBER] - Diah Estingtias; Tantut Susanto; Kholid Rosyidi Muhammad Nur (Penelitian Gizi dan Makanan (The Journal of Nutrition and Food Research), 2019)
Background:The role of family are included role formal and informal. Those roles are required to meet the need of a baby in daily complementary breast feeding. Aside from bearing responsibility in parenting, a family also plays substantive role in meeting nutritional needs of their child for his growth and development. Objectives:To analyze the correlation between the family of role and complementary breast feeding in 6-24 months old baby in Jember, East Java Province of Indonesia. Method:This research applied correlational design and cross-sectionalapproach. The sample was taken using cluster random samplingapproach on 113 participant. The correlation is analyzed using Spearmen Ranktest. Results:The average family of role was categorized as good (Z=1,870; p-value=0.002). At the same time, the average complementary breast feeding practiced in 6-24 months old baby was categorized as fair (89.4%). There were correlation between the family of role and complementary breast feeding in 6-24 months old baby (r= 0.297; p-value=0.001), Conclusions:Family have role to improve complementary breast feeding practiced. To further increase the complementary breast feeding the research give good advice to health workers and community health centers staff are more active in doing counseling regarding complementary feeding according to the age of the baby.